2010
DOI: 10.1007/s11596-010-0119-z
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a new lamin A/C mutation in a chinese family affected with atrioventricular block as the prominent phenotype

Abstract: Even though mutations in LMNA have been reported in patients with typical dilated cardiomyopathy (DCM) and atrioventricular block (AVB) previously, the purpose of this study was to disclose this novel genetic abnormality in one Chinese family with the atypical phenotype of progressive AVB followed by DCM with normal QRS interval. Genome-wide linkage analysis mapped the AVB gene in this family to a marker at chromosome 1q21.2, where the LMNA gene was located. Direct DNA sequence analysis revealed a heterozygous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…At present, only three families with DCM resulting from similar mutations have been identified; the detection of the responsible mutation sites in the investigated family of the present study supports the hypothesis that p.E82K in LMNA may exhibit strong pathogenic effects that results in DCM ( 34 36 ). Additionally, studies with larger populations have not been conducted; however, functional studies in vitro have indicated a significant effect on protein function.…”
Section: Discussionsupporting
confidence: 85%
“…At present, only three families with DCM resulting from similar mutations have been identified; the detection of the responsible mutation sites in the investigated family of the present study supports the hypothesis that p.E82K in LMNA may exhibit strong pathogenic effects that results in DCM ( 34 36 ). Additionally, studies with larger populations have not been conducted; however, functional studies in vitro have indicated a significant effect on protein function.…”
Section: Discussionsupporting
confidence: 85%
“…Surprisingly, both Lmna H222P/+ and Lmna N195K/+ mice were found to have a phenotype and life expectancy similar to the wild-type [26,27]. Cells derived from both Lmna -/-and Lmna N195K/N195K mice were observed to have damaged and misshapen nuclei, showed increased fragility under mechanical strain and impaired gene transcription [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Another model for DCM-CD is transgenic mice with cardiac-specific expression of the p.E82K lamin A/C variant ( Lmna E82K ) [115]. This variant results from an exon 1 LMNA mutation identified in a Chinese family with DCM-CD (atrioventricular block) [116,117]. Transgenics were comparable to their non-transgenic siblings at birth and at a young age [115].…”
Section: Animal Modelsmentioning
confidence: 99%